Preparation and application of low-defect Prussian blue analogue

By introducing solid regulator NPC in the preparation of Prussian blue analog, the nucleation rate is slowed down and crystal defects are repaired. The prepared Zn-PBA-NPC significantly improves the adsorption performance and stability, and solves the crystal defects in the preparation of traditional PBAs and the problem of too small size, efficient Rb+ adsorption and recovery are achieved.

CN119160916APending Publication Date: 2024-12-20BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411321855.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional Prussian blue analogs (PBAs) are prone to crystal defects and too small crystal size during the preparation process, which affects their adsorption performance and recovery difficulty. The adsorption capacity of the carrier material is poor, reducing the overall adsorption performance.

Method used

Using a preparation method of low-deficiency Prussian blue analog, ZIF-8 is formed by slowly adding Zn(NO3)2·6H2O and 2-methylimidazole solutions at room temperature, and after pyrolysis in N2 environment, K3Fe(CN)6 and K3C6H5O7 were mixed and slowly added to the solution. The solid regulator NPC was used to slow down the nucleation rate and repair crystal defects to obtain Zn-PBA-NPC.

Benefits of technology

Improve the crystal size and adsorption capacity of Zn-PBA-NPC, increase the content of alkali metal K and ion exchange sites, improve the stability and adsorption performance of the material, especially show excellent performance in a wide pH range. Anti-interference and rapid adsorption removal rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160916A_ABST
    Figure CN119160916A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of crystal materials, in particular to preparation and application of a low-defect Prussian blue analogue. The method comprises the following steps: preparing ZIF-8 by using a methanol solution of Zn (NO3) 2.6 H2O and 2-methylimidazole, pyrolyzing the ZIF-8 in an N2 environment, preparing a solid regulator NPC, mixing the NPC with a K3Fe (CN) 6 aqueous solution to obtain a suspension A, dissolving Zn (NO3) 2.6 H2O and K3C6H5O7 in deionized water to obtain a solution B, and dropwise adding the suspension A into the solution B to prepare the low-defect Prussian blue analogue. The material is large in crystal size, generates twin crystals at the same time, has good acid-base stability and thermal stability, has few crystal defects, high alkali metal K ion content and multiple ion exchange sites, has relatively large adsorption capacity and relatively high adsorption and removal rate on Rb < + > in a water body, and has good ion interference resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crystal materials, in particular to the preparation and application of a low-defect Prussian blue analogue. Background Art

[0002] As a rare and precious metal, rubidium is widely used in atomic clocks, chemical catalysis, special glass, biomedicine and other fields due to its excellent chemical activity and photoelectric effect. Rubidium resources mainly exist in solid minerals and salt lakes. Due to its low grade and complex composition, it is difficult to mine. + Widely present in ore leaching wastewater and urban sewage, it will cause long-term impact on the ecological environment, and due to Rb + Chemical properties and Na + , K + Similar, making Rb + It is easily absorbed by organisms, causing glomerular damage, reproductive system damage and cancer, thus having adverse effects on human health. + It is crucial for resource recovery and environmental protection.

[0003] Currently, Rb + The main recovery and treatment technologies are membrane separation, extraction and adsorption. Adsorption is considered to be the most promising and effective method due to its simple operation, low energy consumption and environmental protection. Prussian blue analogs (PBAs) have the characteristics of good selectivity, large adsorption capacity, good stability, fast adsorption kinetics and excellent regeneration performance. The general formula of PBAs is A x M a [M b (CN)6] z nH2O, where A represents the alkali metal inserted into the framework gap, M a and M b represents a transition metal connected by a cyano ligand. PBAs are mostly synthesized by a simple coprecipitation method. During the synthesis process, the nucleation rate of PBAs may be too fast. This rapid nucleation often leads to a large number of [M b (CN)6] vacancies, affecting its stability and reducing the alkali metal content, which has a negative impact on the adsorption performance. In addition, PBAs with too small a crystal size are easy to disperse in water, increasing the difficulty of recovery. In order to reduce the dispersion of PBAs, functional materials are often used to fix PBA nanoparticles, such as polymer matrices, layered hydroxides, clays and magnetic materials. However, these carrier materials have poor adsorption capacity and will essentially reduce the overall adsorption performance. To this end, we proposed a new method for preparing PBAs to improve their crystal structure and improve the adsorption performance of PBAs. Summary of the invention

[0004] The present invention provides a preparation method and application of a low-defect Prussian blue analogue, which solves the problems of crystal defects and too small crystal size caused by a traditional PBA preparation method.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] A method for preparing a low-defect Prussian blue analogue comprises the following steps:

[0007] S1. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol respectively. After they are fully dissolved, 2+ The methanol solution was slowly added to the 2-methylimidazole methanol solution, stirred at room temperature for 24 to 36 hours, and the white solid powder was collected by centrifugation, washed with methanol for multiple times, and dried at 353K for 24 to 26 hours to obtain ZIF-8.

[0008] Wherein, the mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:(0.85-1.26);

[0009] Preferably, the mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:1.04;

[0010] Wherein, the Zn 2+ Zn in methanol solution 2+ The concentration is 0.12-0.15 mmol / mL, and the concentration of 2-methylimidazole in the 2-methylimidazole methanol solution is 0.45-0.55 mmol / mL;

[0011] Preferably, Zn 2+ Zn in methanol solution 2+ The concentration is 0.13 mmol / mL, and the concentration of 2-methylimidazole in the 2-methylimidazole methanol solution is 0.5 mmol / mL;.

[0012] S2. The ZIF-8 prepared in S1 was pyrolyzed at 1073 K in a N2 environment at a heating rate of 5 K / min for 5 to 6 h, and the black granular products were collected, washed with 1 mol / L HNO3 and deionized water, and dried at 353 K for 24 to 26 h to obtain NPC.

[0013] S3. The NPC prepared in S2 is mixed with a K3Fe(CN)6 aqueous solution with a concentration of 35 to 45 mmol / L to obtain a suspension A, Zn(NO3)2·6H2O and K3C6H5O7 are dissolved in deionized water to obtain a solution B, and the suspension A is slowly added dropwise to the solution B in a volume ratio of 1:1, and the mixture is stirred at room temperature for 6 to 8 hours, the product is collected by filtration, washed with deionized water and methanol, and dried at 353 K for 24 to 26 hours to obtain Zn-PBA-NPC, which is the low-defect Prussian blue analogue.

[0014] Wherein, the concentration of the K3Fe(CN)6 aqueous solution is preferably 40mmol / L;

[0015] Wherein, the concentration of NPC in suspension A is 0.9-1.1 g / L;

[0016] Preferably, the concentration of NPC in suspension A is 1 g / L;

[0017] Wherein, the concentration of Zn(NO3)2·6H2O in solution B is 16.2-19.7 g / L;

[0018] Preferably, the concentration of Zn(NO3)2·6H2O in solution B is 17.9 g / L;

[0019] Wherein, the concentration of K3C6H5O7 in solution B is 8.7-10.7 g / L;

[0020] Preferably, the concentration of K3C6H5O7 in solution B is 9.7 g / L.

[0021] The present invention provides a low-defect Prussian blue analogue obtained by the above method, and also provides the above low-defect Prussian blue analogue, which has a high affinity for Rb + The adsorption capacity is 180-220 mg / g.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) When preparing the crystal, a solid regulator NPC is introduced. During the reaction, NPC can react with Fe(CN)6 3- The interaction slows down the nucleation rate of the crystals, promotes the increase of crystal size and the formation of twins, so that the size of the prepared Zn-PBA-NPC crystals is significantly increased, the difficulty of recovery after adsorption application is reduced and the adsorption capacity is increased.

[0024] (2) During the reaction, under the reducing effect of the solid regulator NPC, Fe(CN)6 3- Reduced to Fe(CN)6 4-,Fe(CN)6 4- The crystal defects are self-repaired, so that the defects of the prepared Zn-PBA-NPC crystal are reduced; then the alkali metal K is transferred into the material structure, which improves the material stability and the number of ion exchange sites, making the material have good acid-base stability and thermal stability. In addition, the alkali metal K ion content is high and the ion exchange sites are many, which makes the Rb + The adsorption capacity is increased and the adsorption removal rate is fast.

[0025] (3) Zn-PBA-NPC has strong anti-ion interference ability and exhibits excellent anti-interference property in a wide pH range. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (a) is the PXRD pattern of the intermediate product and the final product; (b) is the XPS spectra of Zn-PBA and Zn-PBA-NPC; (c) is the high-resolution XPS spectra of Fe 2p of Zn-PBA and Zn-PBA-NPC; (d) is the Fourier transform infrared spectra of the intermediate product and the final product; (e) is the thermogravimetric curves of Zn-PBA and Zn-PBA-NPC; (f) is the iron ion leaching of Zn-PBA and Zn-PBA-NPC at different pH values;

[0027] Figure 2 (a)-(d) are SEM images of ZIF-8, NPC, Zn-PBA and Zn-PBA-NPC, respectively; (e) and (f) are TEM images of Zn-PBA-NPC; (g) and (h) are EDS images of C, N, O, K, Fe and Zn elements of Zn-PBA and Zn-PBA-NPC, respectively;

[0028] Figure 3 (a) is the intermediate product and the final product for Rb + (b) is the effect of Zn-PBA-NPC dosage on adsorption capacity and removal rate (initial concentration 52 mg / L; temperature 298 K); (c) is the adsorption isotherm of Zn-PBA-NPC; (d) is the adsorption kinetics of Zn-PBA-NPC at different initial concentrations;

[0029] Figure 4 (a) The effect of Zn-PBA-NPC on Rb at different pH values + (b) The adsorption of Zn-PBA-NPC on Rb in a mixed solution of Na, K, Ca, Mg, and Rb. + Adsorption conditions;

[0030] Figure 5 (a) Zn-PBA-NPC adsorbs Rb+ PXRD before and after; (b) is Zn-PBA-NPC after adsorption of Rb + XPS spectra before and after; Figure (c) is the XPS spectra of Zn-PBA-NPC after adsorption of Rb + High-resolution XPS spectra of K 2p before and after; (d) is the high-resolution XPS spectra of Rb in solution + and K + Changes in concentration over time;

[0031] Figure 6 Zn-PBA-NPC adsorbs Rb + Schematic diagram of the mechanism. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing a low-defect Prussian blue analog Zn-PBA-NPC comprises the following steps:

[0035] S1. Dissolve 5.95 g of Zn(NO3)2·6H2O and 6.16 g of 2-methylimidazole in 150 mL of methanol. After they are fully dissolved, 2+ The methanol solution was slowly added to the 2-methylimidazole methanol solution, stirred at room temperature for 24 h, and the white solid powder was collected by centrifugation, washed with methanol for multiple times, and dried at 353 K for 24 h to obtain ZIF-8;

[0036] S2, pyrolyzing the ZIF-8 prepared in step S1 at 1073 K for 5 h in a N2 environment at a heating rate of 5 K / min, collecting the black granular product, washing it with 1 mol / L HNO3 and deionized water, and drying it at 353 K for 24 h to obtain NPC;

[0037] S3. Take 0.1 g of NPC prepared in step S2 and mix it with 100 mL of 40 mmol / L K3Fe(CN)6 aqueous solution to obtain suspension A. Dissolve 1.79 g of Zn(NO3)2·6H2O and 0.97 g of K3C6H5O7 in 100 mL of deionized water to obtain solution B. Slowly add suspension A dropwise to solution B, stir the mixture at room temperature for 6 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 24 h to obtain a low-defect Prussian blue analogue Zn-PBA-NPC.

[0038] Example 2

[0039] A method for preparing a low-defect Prussian blue analog Zn-PBA-NPC comprises the following steps:

[0040] S1. Dissolve 5.36 g of Zn(NO3)2·6H2O and 6.75 g of 2-methylimidazole in 150 mL of methanol. After they are fully dissolved, 2+ The methanol solution was slowly added to the 2-methylimidazole methanol solution, stirred at room temperature for 30 h, and the white solid powder was collected by centrifugation, washed with methanol for multiple times, and dried at 353 K for 25 h to obtain ZIF-8;

[0041] S2, pyrolyzing the ZIF-8 prepared in step S1 at 1073 K for 5.5 h in a N2 environment at a heating rate of 5 K / min, collecting the black granular product, washing it with 1 mol / L HNO3 and deionized water, and drying it at 353 K for 25 h to obtain NPC;

[0042] S3. Take 0.09 g of NPC prepared in step S2 and mix it with 100 mL of 35 mmol / L K3Fe(CN)6 aqueous solution to obtain suspension A. Dissolve 1.62 g of Zn(NO3)2·6H2O and 1.07 g of K3C6H5O7 in 100 mL of deionized water to obtain solution B. Slowly add suspension A dropwise to solution B, stir the mixture at room temperature for 7 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 25 h to obtain a low-defect Prussian blue analogue Zn-PBA-NPC.

[0043] Example 3

[0044] A method for preparing a low-defect Prussian blue analog Zn-PBA-NPC comprises the following steps:

[0045] S1. Dissolve 6.53 g of Zn(NO3)2·6H2O and 5.55 g of 2-methylimidazole in 150 mL of methanol. After they are fully dissolved, 2+ The methanol solution was slowly added to the 2-methylimidazole methanol solution, stirred at room temperature for 36 h, and the white solid powder was collected by centrifugation, washed with methanol for multiple times, and dried at 353 K for 26 h to obtain ZIF-8;

[0046] S2, pyrolyzing the ZIF-8 prepared in step S1 at 1073 K for 6 h in a N2 environment at a heating rate of 5 K / min, collecting the black granular product, washing it with 1 mol / L HNO3 and deionized water, and drying it at 353 K for 26 h to obtain NPC;

[0047] S3. Take 0.11 g of NPC prepared in step S2 and mix it with 100 mL of 45 mmol / L K3Fe(CN)6 aqueous solution to obtain suspension A. Dissolve 1.97 g of Zn(NO3)2·6H2O and 0.87 g of K3C6H5O7 in 100 mL of deionized water to obtain solution B. Slowly add suspension A dropwise to solution B, stir the mixture at room temperature for 8 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 26 h to obtain a low-defect Prussian blue analogue Zn-PBA-NPC.

[0048] Example 4

[0049] A method for preparing a low-defect Prussian blue analog Zn-PBA-NPC comprises the following steps:

[0050] S1. Dissolve 5.62 g of Zn(NO3)2·6H2O and 5.23 g of 2-methylimidazole in 135 mL of methanol. After they are fully dissolved, 2+ The methanol solution was slowly added to the 2-methylimidazole methanol solution, stirred at room temperature for 28 h, and the white solid powder was collected by centrifugation, washed with methanol for multiple times, and dried at 353 K for 24.5 h to obtain ZIF-8;

[0051] S2, pyrolyzing the ZIF-8 prepared in step S1 at 1073 K for 5 h in a N2 environment at a heating rate of 5 K / min, collecting the black granular product, washing it with 1 mol / L HNO3 and deionized water, and drying it at 353 K for 24.5 h to obtain NPC;

[0052] S3. Take 0.094 g of NPC prepared in step S2 and mix it with 90 mL of 38 mmol / L K3Fe(CN)6 aqueous solution to obtain suspension A. Dissolve 1.7 g of Zn(NO3)2·6H2O and 0.9 g of K3C6H5O7 in 90 mL of deionized water to obtain solution B. Slowly add suspension A dropwise to solution B, stir the mixture at room temperature for 6.5 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 25.5 h to obtain a low-defect Prussian blue analogue Zn-PBA-NPC.

[0053] Example 5

[0054] A method for preparing a low-defect Prussian blue analog Zn-PBA-NPC comprises the following steps:

[0055] S1. Dissolve 6.45 g of Zn(NO3)2·6H2O and 6.53 g of 2-methylimidazole in 165 mL of methanol. After they are fully dissolved, 2+The methanol solution was slowly added to the 2-methylimidazole methanol solution, stirred at room temperature for 32 h, and the white solid powder was collected by centrifugation, washed with methanol for multiple times, and dried at 353 K for 25.5 h to obtain ZIF-8;

[0056] S2, pyrolyzing the ZIF-8 prepared in step S1 at 1073 K for 5 h in a N2 environment at a heating rate of 5 K / min, collecting the black granular product, washing it with 1 mol / L HNO3 and deionized water, and drying it at 353 K for 25.5 h to obtain NPC;

[0057] S3. Take 0.107 g of NPC prepared in step S2 and mix it with 110 mL of 42 mmol / L K3Fe(CN)6 aqueous solution to obtain suspension A. Dissolve 1.88 g of Zn(NO3)2·6H2O and 1.02 g of K3C6H5O7 in 110 mL of deionized water to obtain solution B. Slowly add suspension A dropwise to solution B, stir the mixture at room temperature for 7.5 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 24.5 h to obtain a low-defect Prussian blue analogue Zn-PBA-NPC.

[0058] Comparative Example 1

[0059] A method for preparing a Prussian blue analog Zn-PBA, which differs from Example 1 in that no solid regulator NPC is added, comprises the following steps:

[0060] Take 100 mL of 40 mmol / L K3Fe(CN)6 aqueous solution as solution A, dissolve 1.79 g of Zn(NO3)2·6H2O and 0.97 g of K3C6H5O7 in 100 mL of deionized water to obtain solution B, slowly add solution A dropwise to solution B, stir the mixture at room temperature for 6 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 24 h to obtain the Prussian blue analogue Zn-PBA.

[0061] Comparative Example 2

[0062] A method for preparing a Prussian blue analog Zn-PBA, which differs from Example 2 in that no solid regulator NPC is added, comprises the following steps:

[0063] Take 100 mL of 35 mmol / L K3Fe(CN)6 aqueous solution as solution A, dissolve 1.62 g of Zn(NO3)2·6H2O and 1.07 g of K3C6H5O7 in 100 mL of deionized water to obtain solution B, slowly add solution A dropwise to solution B, stir the mixture at room temperature for 7 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 25 h to obtain the Prussian blue analogue Zn-PBA.

[0064] Comparative Example 3

[0065] A method for preparing a Prussian blue analog Zn-PBA, which differs from Example 3 in that no solid regulator NPC is added, comprises the following steps:

[0066] Take 100 mL of 45 mmol / L K3Fe(CN)6 aqueous solution as solution A, dissolve 1.97 g of Zn(NO3)2·6H2O and 0.87 g of K3C6H5O7 in 100 mL of deionized water to obtain solution B, slowly add solution A dropwise to solution B, stir the mixture at room temperature for 8 h, collect the product by filtration, wash with deionized water and methanol, and dry at 353 K for 26 h to obtain the Prussian blue analogue Zn-PBA.

[0067] The intermediate products and final products of Examples 1-3 and Comparative Examples 1-3 were characterized. Figure 1 and Figure 2 .

[0068] Figure 1 As shown in (a), the synthesized ZIF-8 is completely consistent with the simulated PXRD, indicating that ZIF-8 was successfully prepared. NPC shows a characteristic broad peak of graphite at 2θ=26°. In addition, due to the different alkali metal K contents, the simulated diffraction peaks of Zn-PBA and Zn3(Fe(CN)6)2 are consistent. The simulated diffraction peaks of Zn-PBA-NPC are consistent with those of K2Zn3(Fe(CN)6)2, indicating that the alkali metal K content in Zn-PBA-NPC is higher than that in Zn-PBA.

[0069] Figure 1 (b) shows that the elemental composition of Zn-PBA is the same as that of Zn-PBA-NPC. However, Zn-PBA contains almost no alkali metal K. This difference is due to the fact that the solid regulator NPC is not added, which leads to excessive reaction speed and causes Zn-PBA crystal defects. Figure 1 (c) It can be seen that due to the reducing properties of NPC, [Fe(CN)6] 3- Reduction to [Fe(CN)6] 4- , the generated [Fe(CN)6] 4-The crystal defects are self-repaired and the alkali metal K is simultaneously introduced.

[0070] Figure 1 (d) The 421 cm -1 The peak at 1611 cm-1 is Zn-N, which indicates that Zn is coordinated with 2-methylimidazole, indicating the correct structure of ZIF-8. -1 The C=N bond at 1300cm -1 The NH bond at 600 cm-1 in Zn-PBA-NPC and Zn-PBA -1 and 2097cm -1 The peaks are the characteristic peaks of C-Fe and C≡N respectively.

[0071] Figure 1 As shown in (e) and 1(f), Zn-PBA-NPC has significantly better thermal stability and acid-base stability than Zn-PBA.

[0072] Figure 2 It is clearly shown that Zn-PBA-NPC has the morphology of large-sized twins. In addition, the EDS element distribution further shows that the alkali metal K content of Zn-PBA-NPC is higher than that of Zn-PBA.

[0073] Test Example 1

[0074] The intermediate product and the final product prepared in Example 1 and Comparative Example 1 were subjected to adsorption of Rb + Experiment, while analyzing the effect of Zn-PBA-NPC prepared in Example 1 on Rb + Take several 5 mg samples and add them into 10 mL of Rb with a certain initial mass concentration. + In the solution, oscillate and adsorb for a certain period of time under certain temperature conditions, take samples, and use inductively coupled plasma optical emission spectrometer (ICP-OES, Agilent 5800) to measure the ion concentration, so as to calculate the adsorption amount and removal efficiency and draw the adsorption isotherm and adsorption kinetic curve. The test results are shown in Figure 3 The adsorption mechanism is shown in Figure 6 .

[0075] The samples before and after adsorption were characterized. Figure 5 .

[0076] Test Example 2

[0077] The Zn-PBA-NPC prepared in Example 1 was subjected to adsorption of Rb at different pH values. +In the experiment, 5 mg of sample was taken and added to a solution with a pH value of 2 to 12 (0.1 mol / L HCl and 0.1 mol / L NaOH were used to adjust the pH value of the solution). After oscillation and adsorption for a certain period of time, samples were taken and the ion concentration was measured by inductively coupled plasma optical emission spectrometry (ICP-OES, Agilent 5800), thereby calculating the adsorption amount. The test results are shown in Figure 4 (a).

[0078] The Zn-PBA-NPC prepared in Example 1 was subjected to adsorption of Rb under different interfering ion conditions. + In the experiment, 5 mg of sample was taken and added to 10 mL of Rb with a certain initial mass concentration. + The solution contains Na, K, Ca, and Mg interfering ions. The solution is oscillated and adsorbed for a certain period of time under certain temperature conditions. Samples are taken and the ion concentration is measured using an inductively coupled plasma optical emission spectrometer (ICP-OES, Agilent 5800) to calculate the adsorption amount. The test results are shown in Figure 4 (b).

[0079] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and to form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a low-defect Prussian blue analogue, characterized in that: The following steps are involved: S1. Dissolve Zn(NO3)2·6H2O and 2-methylimidazole in methanol respectively. 2+ The methanol solution is added to the 2-methylimidazole methanol solution, stirred, and the solid powder is collected by centrifugation, washed, and dried to obtain ZIF-8; S2, pyrolyzing the ZIF-8 prepared in S1 in a N2 environment, collecting the product, washing, and drying to obtain NPC; S3. Mix the NPC prepared in S2 with a K3Fe(CN)6 aqueous solution to obtain a suspension A, dissolve Zn(NO3)2·6H2O and K3C6H5O7 in deionized water to obtain a solution B, add the suspension A dropwise to the solution B, stir, collect the product by filtration, wash, and dry to obtain Zn-PBA-NPC, which is the low-defect Prussian blue analogue.

2. The preparation method according to claim 1, characterized in that: The mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole in step S1 is 1:(0.85-1.26).

3. The preparation method according to claim 1, characterized in that: Step S1: Zn 2+ Zn in methanol solution 2+ The concentration is 0.12-0.15 mmol / mL, and the concentration of 2-methylimidazole in the 2-methylimidazole methanol solution is 0.45-0.55 mmol / mL.

4. The preparation method according to claim 1, characterized in that: The stirring time in step S1 is 24 to 36 hours at room temperature, the washing is washing with methanol, and the drying is drying at 353K for 24 to 26 hours.

5. The preparation method according to claim 1, characterized in that: The pyrolysis in step S2 is performed at 1073 K for 5 to 6 h, the washing is performed using 1 mol / L HNO3 and deionized water, and the drying is performed at 353 K for 24 to 26 h.

6. The preparation method according to claim 1, characterized in that: The concentration of the K3Fe(CN)6 aqueous solution in step S3 is 35-45 mmol / L; the concentration of the NPC in suspension A is 0.9-1.1 g / L, the concentration of the Zn(NO3)2·6H2O in solution B is 16.2-19.7 g / L, the concentration of the K3C6H5O7 in solution B is 8.7-10.7 g / L, and the volume ratio of the suspension A to the solution B is 1:

1.

7. The preparation method according to claim 1, characterized in that: The stirring in step S3 is stirring at room temperature for 6 to 8 hours, the washing is washing with deionized water and methanol, and the drying is drying at 353K for 24 to 26 hours.

8. A low-defect Prussian blue analogue obtained by the preparation method according to any one of claims 1 to 7.

9. The low-defect Prussian blue analogue of claim 8 absorbs Rb in water + application.

Citation Information

Cited By

  • Anion-deficient prussian blue analogue, preparation method thereof and application of anion-deficient prussian blue analogue in cesium adsorption

    CN121516881A